Synthesis of superconductive TaN thin films by reactive DC sputtering - Nieto Sánchez, Amanda G.; Guzmán, Mario; Conde Gallardo, A.; Contreras, O. (My University, 2022)
Superconductive TaN thin flms synthesized with reactive direct current (DC) sputtering were grown on silicon substrates at 600°C for 60 min with variations of the N2 gas fow ratio (RN2). The microstructure of the thin flms was analyzed by transmission electron microscopy (TEM), observing a TaN polycrystalline structure constructed by stacked (200) and (111) planes. The surface morphology for almost all samples was relatively smooth with the exception of the flm deposited using the highest RN2 which showed a considerably higher roughness. Chemical composition was determined by x-ray photoelectron spectroscopy (XPS) analysis. It was revealed that the thin flms consist of a tantalum nitride compound with a TaNx stoichiometry ranging from 0.43 < x < 1.35. The crystallographic results of the obtained flms showed that it evolved from face centered cubic (FCC) TaN structure, preferentially oriented along <111> for low RN2, to <200> preferred orientation and later to a crystal phase combination (FCC TaN and tetragonal Ta3N5) as RN2 ratios was increased. The electrical resistivity of the TaN thin flms presented a clear dependence on the stoichiometry which increased considerably with the nitrogen content. All samples but the one synthesized with the highest RN2 (which presented an insulation electrical behavior) exhibited the typical stepped superconductor transition, and their superconductive transition temperature (Tc) was reduced as the preferred orientation changed from <111> to the <200> direction. This was correlated with RN2 and its efect on the crystal growth. RESUMEN Películas delgadas de TaN superconductoras sintetizadas con pulverización catódica de corriente continua (CC) reactiva se cultivaron en sustratos de silicio a 600 ° C durante 60 min con variaciones de la relación de flujo de gas N2 (RN2). La microestructura de las películas delgadas se analizó mediante microscopía electrónica de transmisión (TEM), observándose una estructura policristalina TaN construida por planos apilados (200) y (111). La morfología de la superficie para casi todas las muestras fue relativamente suave, con la excepción de la película depositada usando el RN2 más alto que mostró una rugosidad considerablemente mayor. La composición química se determinó mediante análisis de espectroscopía de fotoelectrones de rayos X (XPS). Se reveló que las películas delgadas consisten en un compuesto de nitruro de tantalio con una estequiometría TaNx que oscila entre 0,43 < x < 1,35. Los resultados cristalográficos de las películas obtenidas mostraron que evolucionó desde una estructura TaN cúbica centrada en las caras (FCC), orientada preferentemente a lo largo de <111> para RN2 bajo, a una orientación preferida <200> y luego a una combinación de fase cristalina (FCC TaN y tetragonal Ta3N5 ) a medida que aumentaban las proporciones de RN2. La resistividad eléctrica de las películas delgadas de TaN presentó una clara dependencia con la estequiometría que aumentó considerablemente con el contenido de nitrógeno. Todas las muestras excepto la sintetizada con el RN2 más alto (que presentó un comportamiento eléctrico de aislamiento) exhibieron la típica transición superconductora escalonada, y su temperatura de transición superconductora (Tc) se redujo a medida que la orientación preferida cambiaba de <111> a <200>. . Esto se correlacionó con RN2 y su efecto sobre el crecimiento de cristales.
Journal of electronic materials
Keywords: Thin films; Superconductor; Electrical properties; Nitrides; Sistema